New record of amphipod Elasmopus alkhiranensis (Myers and Momtazi, 2015) from the breakwaters at Faw city, Iraq - Nabaa Auda; Amaal Yasser; Murtada Naser (Journal of Fauna Biodiversity, 2025)
One male specimen of the new record amphipod Elasmopus alkhiranensis (Myers and Momtazi, 2015) previously recorded from Iraq was discovered. The specimen was collected alive from the intertidal zone at the breakwaters of Faw city on the Iraqi coast. Although this species is widespread in the Persian-Arabian Gulf, our study is the first to report it along the Iraqi coast.